A Triptycene‐Based Porous Organic Polymer that Exhibited High Hydrogen and Carbon Dioxide Storage Capacities and Excellent CO2/N2 Selectivity. Issue 5 (5th May 2015) - Lu, Xi‐Long; Zhou, Tian‐You; Wu, Doufeng; Wen, Qiang; Zhao, Xin; Li, Qiaowei; Xiang, Qun; Xu, Jia‐Qiang; Li, Zhan‐Ting
Abstract A novel porous organic polymer (POP) has been constructed through the condensation of triptycene tricatechol and 1, 3, 5‐benzenetris(4‐phenylboronic acid). This triptycene‐based POP exhibited high H2 uptake (up to 1.84 wt% at 77 K, 1 bar), large CO2 adsorption capacity (up to 18.1 wt% at 273K, 1 bar), and excellent CO2/N2 adsorption selectivity (up to 120/1). The influence of solvent on the gas adsorption performance of the POP has also been investigated.